Analytical Simulation of Linear Comparison of Temperature Changes Versus Time in the Heat Equilibrium Process of Mixing Two Liquids - Goenawan, Stephanus Ivan (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
The explanation of the concept of entropy which explains that the increase in disorder in a closed system that works in advancing time comes from the second Law of Thermodynamics. In its development, Law of Thermodynamics 2 was enriched by the presence of Law of Thermodynamics 2.1 which states that the average entropy process in the forward direction will be the same or smaller than in the backward direction. The meaning of the entropy averaging process in the backward direction is that the entropy averaging process is in the forward direction but works on a heat function that mirrors the previous one, namely the heat function over time in the forward direction. Furthermore, by utilizing the Law of Thermodynamics 2.1, the results of analytical simulations can be seen comparing the level of linearity of changes in temperature over time in the process of heat flow towards thermal equilibrium in the mixing of two liquids. The results of this analytical comparison show one of the benefits of developing the second Law of Thermodynamics, namely Law of Thermodynamics 2.1.